256 Single-agent zalifrelimab (anti-CTLA-4) shows clinical benefit in rare tumors – case report from phase 2 study (NCT03104699). (9th November 2020) - Perez, Cesar; Wesolowski, Robert; Wilky, Breelyn; Feliu, Waldo Ortuzar; Zhang, Hong; Shapiro, Irina; Wijatyk, Anna; Kaleta, Remigiusz; Trent, Jonathan
Abstract : Background: Zalifrelimab is a fully human monoclonal antibody against cytotoxic T-lymphocyte -associated protein 4 (CTLA-4). Preliminary data demonstrated clinical benefit and tolerability, as monotherapy, in patients with recurrent solid tumors including rare tumor types. Previously presented Phase I data reported one durable complete response in recurrent cutaneous angiosarcoma (cAS). 1 Here we report additional clinical responses from an ongoing Phase 2 study of zalifrelimab monotherapy including clinical benefit in rare solid tumors. Methods: In an ongoing, phase 2 study (NCT03104699 ), the safety and efficacy of zalifrelimab, as monotherapy, was evaluated in patients who progressed on prior anti-PD-1/L1 treatment. All patients were treated intravenously (IV) with zalifrelimab at 1 mg/kg every 3 weeks until disease progression or up to 2 years. Results: Overall, 44 patients were treated and 29 patients were response-evaluable at the time of report. In patients with refractory solid tumors treated with zalifrelimab, we report a disease control rate (CR, PR, and SD) of 51.7%, objective response rate (ORR) of 10.3% (3/29), disease stabilization of 41.3% (12/29). Clinical activity was observed in five solid tumors considered rare, including; cAS (N=1), glucagonoma (N=1), chondrosarcoma (N=1), spindle-cell sarcoma (N=1) and fibroblastic sarcoma (N=1). In these rare tumors, durable partial responses of 45 and 30 weeks were observed in cAS of the scalp with lymph node metastases and glucagonoma, respectively. Both patients remain on zalifrelimab with no evidence of disease progression. Additionally, durable disease stabilization was observed in a patient with spindle-cell sarcoma. Patients with chondrosarcoma and fibroblastic sarcoma progressed on therapy. Zalifrelimab was well tolerated with the most commonly reported treatment-related adverse events including fatigue, nausea, anemia, diarrhea and vomiting, consistent with the drug class. Most events were mild or moderate and resolved with standard treatments. Conclusions: Our data demonstrates the potential for Zalifrelimab to promote meaningful clinical benefit in difficult to treat tumors, including patients that progress on prior PD-1/PD-L1 therapy or chemotherapy. Notably, responses were observed in rare tumor types such as recurrent cutaneous angiosarcoma and glucagonoma. Treatment with zalifrelimab is safe and well tolerated in patients with advanced malignancies. Trial Registration: NCT03104699. Reference: Vaia Florou, Andrew E Rosenberg, Eric Wieder, Krishna V. Komanduri, Despina Kolonias, Mohamed Uduman, John C Castle, Jennifer S. Buell, Jonathan C. Trent and Breelyn A. Wilky Journal for Immunotherapy of Cancer 2019 7:213.